Accuracy of smartwatches in predicting distance running performance - Jiansong Dai; Gangrui Chen; Zhonghe Gu; Yuxuan Qi; Kai Xu (Frontiers in Sports and Active Living)
ObjectiveThis study examined the accuracy of smartwatches in predicting running performance.MethodsA total of 154 amateur runners (123 males and 31 females) were recruited. After wearing the HUAWEI WATCH GT Runner for a minimum of six weeks, the runners' actual completion times for 5 km, 10 km, and half marathon distances were measured, resulting in 288 test instances. The predicted completion times for the same distances displayed on the watch on the test day were recorded simultaneously.ResultsThe actual and predicted performances for the 5, 10, and 21.1 km distances were highly correlated, with r ≥ 0.95 (p < 0.001) and r2 ≥ 0.9 for all three distances, an error rate between the measured and predicted values of less than 3%, and intraclass correlation coefficient ≥0.9. The bias ± 95% limits of agreement were −20.4 ± 44.2 s for 5 km, 4.1 ± 299.1 s for 10 km, and 143.8 ± 400.4 s for the half marathon.ConclusionsThis study confirmed that the smartwatch exhibits high precision in predicting 5 km, 10 km, and half marathon performances, with an accuracy exceeding 97%. The performance prediction features of smartwatches can effectively guide amateur runners in setting reasonable competition goals and preparing for races.